(untitled) (SCIENCE TIME JOURNAL, 2026)
Language contact is one of the central factors influencing linguistic development in multilingual societies. Continuous interaction between linguistic communities leads to the emergence of various phenomena such as bilingualism, interference, borrowing, and language convergence. One of the most noticeable outcomes of language contact is code-switching, which refers to the alternation between languages within a communicative act. This article examines code-switching from the perspective of contact linguistics and bilingual communication. The study focuses on theoretical approaches to language contact, the role of bilingualism in linguistic interaction, and the sociolinguistic conditions that facilitate language alternation in speech. The results demonstrate that code-switching should be understood as a natural consequence of bilingual communication and as an important mechanism reflecting the dynamic interaction of linguistic systems.